Clinical evaluation of postoperative analgesia provided by ketoprofen associated with intravenous or epidural morphine in bitches undergoing ovariosalpingohysterectomy - Gabriela Carvalho Aquilino Santos; Rosana Maria de Oliveira Clark; Roueda Abou Said; Christhiano Midlej Silva Ramos; Alexandre Dias Munhoz (Semina: Ciências Agrárias, 2015)
Multimodal analgesia refers to the practice of combining multiple analgesic drug classes or techniques to target different points along the pain pathway. The objective of this work was to evaluate clinically if ketoprofen associated or not with intravenous or epidural morphine provided adequate postoperative analgesia in bitches undergoing ovariosalpingohysterectomy (OSH). Forty healthy female dogs, weighing 10.7±6.0 kg, sedated with acepromazine (0.05mg kg –1.iv), induced with propofol (5 mg.kg-1. iv) and maintained with isoflurane anesthesia, were distributed into four groups of 10 animals each. After stabilization of inhalation anesthesia, the bitches in Miv and CMiv groups received 0.2 mg.kg-1 of morphine intravenously diluted in 10ml of saline; whereas Mep and CMep groups received 0.1mg.kg-1 of epidural morphine. Thirty minutes after premedication, 2.0mg.kg-1.im of ketoprofen was administered in groups CMiv and CMep. Heart and respiratory rate, systolic blood pressure, and rectal temperature were measured. The degree of analgesia was assessed by a blind study in the following 6 hours after surgery, using a descriptive scale and a scale composed by physiologic and behavioral parameters. An statistical analysis was performed using the Tukey-Kramer test and nonparametric Kruskal-Wallis test, with statistical significance of 5%. There was no important difference between the four groups regarding postoperative analgesia, heart and respiratory rate, systolic blood pressure and rectal temperature. According to the results it can be concluded that the use of ketoprofen associated with intravenous or epidural morphine provided adequate and safe analgesia in the first six hours of postoperative in bitches undergoing ovariohysterectomy, suggesting that there was no analgesic potentiation when both agents were combined.